Innovation process in publicly traded companies of Serra Gaúcha - Dutra, Catherine Chiappin; Pavinato, Cristiano Wagner Tesser; Carrer, Maria Luiza Furlanetto; Camargo, Maria Emília; Olea, Pelayo Munhoz (Revista de Administração da UFSM, 2021)
Purpose - The innovation process is characterized by being continuous and focused mainly on the differentiation of the organizations, aiming at obtaining a competitive advantage. Thus, this study aimed to analyze the innovation process in publicly traded companies of Serra Gaúcha. Design/methodology/approach - A quantitative study was conducted through a survey with descriptive statistical analysis. The questionnaire was prepared based on the study of Floriani, Beuren and Machado (2013) and sent to seven companies from Serra Gaúcha listed on BM&F Bovespa. The analysis was segmented into organizational capabilities, innovation contexts, innovation focus, and enhanced performance. Findings - The results showed that there are procedures in the processes in most companies, and the focus of innovation is especially on products and directed to the market. All organizations use their own resources to execute innovations. Most of the registered patents are in the national sphere, and two companies have not registered any patents in the last two years. Originality/value - Previous studies have not identified any companies from Serra Gaúcha as participants in the innovation process in Brazilian publicly traded companies. Besides, it is impossible to define a profile of the region from the data treatment in previous studies. The proposed study analyzes how the innovation process occurs in publicly traded companies of Serra Gaúcha listed on BM&F Bovespa.